2019
DOI: 10.1155/2019/6972427
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Selected Dairy Products in Sri Lankan Market

Abstract: The purpose of the study was to determine the quality of selected Sri Lankan-marketed dairy products. Four brands of full cream milk powder (FCMP) (imported A and B; local C and D) and three brands of pasteurized milk (PM) attributed to the alphabetical identifies E, F, and G were tested, with raw cow’s milk (CM) as control. Fat, protein, ash, carbohydrate, moisture, and water percentage, total solids (TS), titratable acidity (TA), pH, specific gravity (SG), arsenic content, and total coliform count (TCC) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The TVPC of raw milk increased when the pH of raw milk decreased. This is mainly due to bacterial growth resulting in spoilage of raw milk, which will eventually reduce the pH of the milk as a result of lactic acid production by lactic acid bacteria (Lu et al, 2013;Perera, Munasinghe, & Marapana, 2019). Thus, as expected, the results revealed that the pH of the milk is inversely proportional to the TVPC of the milk.…”
Section: Relationship Between Total Viable Plate Counts (Tvpc) and Th...supporting
confidence: 68%
See 1 more Smart Citation
“…The TVPC of raw milk increased when the pH of raw milk decreased. This is mainly due to bacterial growth resulting in spoilage of raw milk, which will eventually reduce the pH of the milk as a result of lactic acid production by lactic acid bacteria (Lu et al, 2013;Perera, Munasinghe, & Marapana, 2019). Thus, as expected, the results revealed that the pH of the milk is inversely proportional to the TVPC of the milk.…”
Section: Relationship Between Total Viable Plate Counts (Tvpc) and Th...supporting
confidence: 68%
“…Raw milk is an excellent medium for various microbial communities and provides a favourable physiochemical environment for harbouring a wide range of microbial consortiums (Garnier, Valence, & Mounier, 2017;Oliveira, Favarin, Luchese, & Mclntosh, 2015;Perera, Munasinghe, & Marapana, 2019;Sowmya, 2017). The growth of microbiota in raw milk has great concerns regarding the safety and quality of the milk intended for consumption or processing (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%